Knowledge, attitude, and practices (KAP) on community-oriented policing in Malaysian neighbourhoods - Ahmad Suhaimi, Siti Shazwani; Nazuri, Nur Shuhamin; Burhan, Nik Ahmad Sufian; Abdul Rahman, Abdul Razak; Hamsan, Hanina H. (Human Resource Management Academic Research Society, 2021)
The concept of community policing is highlighted as an effort to achieve enhanced level of safety and security that can be sustained through community involvement. In Malaysia, the community-oriented policing has been implemented across neighbourhoods since 1968 under the supervision of the Royal Malaysia Police (PDRM). However, does the local community these days understand the concept and practice? Thus, the current study attempted to determine the levels of knowledge, attitude, and practices, or simply referred to as KAP among local communities that have been exercising community policing. Through a quantitative survey in five major zones in Malaysia, this study confirmed equally high levels of knowledge on and attitude towards community policing, with scores of around 4 based on Likert scale of 1-5. On the other hand, the score was slightly lower for practices, which was around 3.5. This study concluded that in general, the local communities have exercised community policing despite living in busy urban environments. Several policy implications were proposed to ensure the sustainability of community-oriented policing while fostering social cohesion in neighbourhoods in Malaysia.